Paraganglioma of the urinary bladder- a case report - Hassan, Muzammil; Quereshi, Abdul Hafeez (Journal of the Pakistan Medical Association, 2024)
It is very uncommon to discover Paragangliomas in the urinary bladder. These tumours originate from the sympathetic nerves which supply chromaffin cells in the bladder wall. They can be classified as functional or non-functional. If functional, the most common presentations are with hypertensive crisis or post-micturition syncope. A silent paraganglioma of the bladder can be easily misdiagnosed which can result in severe peri-operative morbidity. We present a case of a male patient who was being managed for hypertension for 2-3 years. He presented at The Indus Hospital, Karachi on 7th August 2022 with gross painless haematuria. An ultrasound scan revealed an echogenic lesion arising from base of the urinary bladder, which was treated via Transurethral Resection of Bladder Tumour (TURBT). Histopathological report revealed Paraganglioma of the Bladder. He was later scheduled for Partial Cystectomy (PC) and has been doing well ever since.